Effectiveness of the Implementation of the Sustainable Agricultural Land and Food Protection (LP2B) Policy in North Kuta District, Badung Regency - I Wayan Radana; Ida Ayu Putu Sri Widnyani; I Wayan Astawa (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract The rapid conversion of farmland in North Kuta District led the Badung Regency Government to issue Regional Regulation Number 13 of 2022 on the Protection of Sustainable Agricultural Land and Food (LP2B), aimed at protecting farmland from development and tourism pressures. This study seeks to assess the effectiveness of the Protection of Sustainable Agricultural Land and Food (LP2B) policy in North Kuta, identify the main obstacles to its implementation, and find solutions to address these challenges. Using a qualitative approach, informants were selected through purposive sampling, and data were gathered via observation, interviews, documentation, and field studies. The results show that the Protection of Sustainable Agricultural Land and Food (LP2B) policy in Tibubeneng Village has not been effective due to weak implementation, limited public outreach, low transparency, minimal farmer involvement, and economic interests that conflict with policy goals. Government budget support is still limited to providing seed subsidies, so a more inclusive approach and better communication are needed to make the policy sustainable. Keywords: Land Conversion, Effectiveness, Public Policy